IMPLEMENTATION OF OVERALL EQUIPMENT EFFECTIVENESS TO INCREASE FORKLIFT PRODUCTIVITY AT PT. HAKIM BIMA PRIMA - Muhammad Safii Nasution (Universitas Riau Kepulauan, 2024)
Implementation of Overall Equipment Effectiveness (OEE) in Enhancing Forklift Productivity at PT. Hakim Bima Prima. Utilizing the OEE measurement method to analyze the forklift's performance in terms of availability, performance, and quality. The research shows that by applying OEE, the efficiency of forklift usage can be significantly improved. The practical implication of this study is the increased forklift productivity and reduced maintenance costs. The implementation of OEE on forklifts can be an effective strategy to enhance efficiency and productivity in the company's environment. The objective of this research is to evaluate forklift performance using OEE as the primary framework. Data collection methods involve monitoring operational time, non-productive time, and the success rate of forklift missions from March 2023 to July 2023. The results demonstrate that OEE can be effectively used to identify the primary causes of downtime and optimize forklift usage. The main causes of downtime include maintenance, operational disruptions, and unbalanced workloads. By implementing improvements based on OEE findings, forklift productivity significantly increased, with an average improvement of over 80% during the research period. The application of OEE on forklifts offers manifold benefits, including reduced maintenance costs, increased operational uptime, and more efficient resource utilization. This study provides valuable insights for companies relying on forklifts in their operations, emphasizing the importance of equipment performance monitoring and analysis to enhance overall productivity and efficiency